Biocompatibility of gold and stainless steel chains used for forced eruption of impacted teeth - an in vitro investigation - Zingler, Sebastian; Erber, Ralf; Lux, Christopher J.; Seeberger, Robin (Oral surgery, oral medicine, oral pathology and oral radiology, 2013)
Objective - Surgical approaches for the mobilization of impacted teeth involve the use of gold chains to connect the impacted tooth with the orthodontic appliance. In this study we have compared the local effects gold plated stainless steel with stainless steel specimen using an in vitro model of the gingival mucosa and monolayer cultures of cells of the alveolus. - Study Design - Local effects on differentiation, proliferation, and apoptosis and inflammatory response were tested using organotypic cultures of gingival cells. Cytotoxicity was measured by MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) assays with monolayer cultures of human periodontal cells. - Results - The data obtained in this study could not reveal any differences in favor of using gold plated chains during the mobilization of impacted teeth. - Conclusion - For patients not suffering from allergies against nickel there might be no rationale to favor gold plated chains, as there are no functional aspects to favor gold plated chains over stainless steel chains.